Synthesis and Antimicrobial Activity of New imine Derivatives Containing Drug Molecule - Hussein Faraj Mansour , Diaa; F. Noori , Abbas (Pure Sciences International Journal of Kerbala, 2026)
The research involved the synthesis four of new Schiff base derivatives (SC1, SC3, SC4, SC6) through the condensation reaction of Three amines (drugs) with four aldehydes, all conducted under mild conditions. To validate their chemical structures, the produced compounds were analyzed utilizing spectroscopic methods such as FT-IR, 1H-NMR, and 13C-NMR. The antibacterial activity of Schiff base derivatives was tested against (Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae, Proteus spp., and Staphylococcus aureus) using the agar well diffusion technique. The findings revealed that SC1 was the most powerful and broad-spectrum antibacterial activity of all of the chemicals tested, with inhibition zone widths ranging from 18 to 30 mm, while SC3 showed moderate activity against most tested strains, with the highest activity against E. coli (21 mm) and S. aureus (25 mm). The structure-activity relationship (SAR) research revealed that electron-donating and electron-withdrawing substituents on the aromatic ring affected biological activity. These findings indicate that Schiff bases may be viable candidates for the creation of novel antibacterial medicines.